How we understand others : philosophy and social cognition - Spaulding, Shannon (Routledge focus on philosophy., 2018)
"In our everyday social interactions, we try to make sense of what people are thinking, why they act as they do, and what they are likely to do next. This process is called mindreading. Mindreading, Shannon Spaulding argues in this book, is central to our ability to understand and interact with others. Philosophers and cognitive scientists have converged on the idea that mindreading involves theorizing about and simulating others mental states. She argues that this view of mindreading is limiting and outdated. Most contemporary views of mindreading vastly underrepresent the diversity and complexity of mindreading. She articulates a new theory of mindreading that takes into account cutting edge philosophical and empirical research on in-group/out-group dynamics, social biases, and how our goals and the situational context influence how we interpret others behavior. Spaulding's resulting theory of mindreading provides a more accurate, comprehensive, and perhaps pessimistic view of our abilities to understand others, with important epistemological and ethical implications. Deciding who is trustworthy, knowledgeable, and competent are epistemically and ethically fraught judgments: her new theory of mindreading sheds light on how these judgments are made and the conditions under which they are unreliable. This book will be of great interest to students of philosophy of psychology, philosophy of mind, applied epistemology, cognitive science and moral psychology, as well as those interested in conceptual issues in psychology."--Provided by publisher.